A qualitative study of the interdisciplinary approaches to adolescent spirituality in Australian government schools. Issue 1 (2nd January 2017) - Natsis, Eva
Abstract: The growing body of evidence in education reveals that 'spirituality' as an aspect of learning is largely overlooked in government schools in Australia and consequently, there is a paucity of research investigating whether young people consider spirituality to be an important and worthwhile component of their educational experience. This paper will report on some findings of a PhD study which investigates the spiritual lived experiences of secondary school students. As an interdisciplinary approach to spirituality for adolescents, this paper represents the different ways spirituality is understood across the disciplines and whether young people view themselves to be 'spiritual'. In sharing some of the student narratives, this paper will explore what spirituality means in the context of young peoples' everyday lives. It will also address how schools can play a central role in students' quest for a sense of meaning; and the important role of teachers in this process will also be explored.